Investigating 3R In Vivo Approaches for Bio‐Distribution and Efficacy Evaluation of Nucleic Acid Nanocarriers: Studies on Peptide‐Mimicking Ionizable Lipid. Issue 18 (30th March 2022) - Giselbrecht, Julia; Pinnapireddy, Shashank Reddy; Alioglu, Fatih; Sami, Haider; Sedding, Daniel; Erdmann, Frank; Janich, Christopher; Schulz‐Siegmund, Michaela; Ogris, Manfred; Bakowsky, Udo; Langner, Andreas; Bussmann, Jeroen; et al.
Abstract: Formulations based on ionizable amino‐lipids have been put into focus as nucleic acid delivery systems. Recently, the in vitro efficacy of the lipid formulation OH4:DOPE has been explored. However, in vitro performance of nanomedicines cannot correctly predict in vivo efficacy, thereby considerably limiting pre‐clinical translation. This is further exacerbated by limited access to mammalian models. The present work proposes to close this gap by investigating in vivo nucleic acid delivery within simpler models, but which still offers physiologically complex environments and also adheres to the 3R guidelines (replace/reduce/refine) to improve animal experiments. The efficacy of OH4:DOPE as a delivery system for nucleic acids is demonstrated using in vivo approaches. It is shown that the formulation is able to transfect complex tissues using the chicken chorioallantoic membrane model. The efficacy of DNA and mRNA lipoplexes is tested extensively in the zebra fish ( Danio rerio ) embryo which allows the screening of biodistribution and transfection efficiency. Effective transfection of blood vessel endothelial cells is seen, especially in the endocardium. Both model systems allow an efficacy screening according to the 3R guidelines bypassing the in vitro–in vivo gap. Pilot studies in mice are performed to correlate the efficacy of in vivo transfection. Abstract : Transfection efficacy of mRNA and DNA using the lipoplex formulation, OH4:DOPE, is screened in vivo. In vivo models are focused upon according to the 3R guidelines, namely chick embryo chorioallantoic membrane and zebra fish ( Danio rerio ) embryo. Pilot studies in mice are performed to allow correlations.